Molecular basis and genetic testing strategies for diagnosing 21-hydroxylase deficiency, including CAH-X syndrome - Ja Hye Kim; Gu-Hwan Kim; Han-Wook Yoo; Jin-Ho Choi (Korean Society of Pediatric Endocrinology, 2023)
Congenital adrenal hyperplasia (CAH) is a group of autosomally recessive disorders that result from impaired synthesis of glucocorticoid and mineralocorticoid. Most cases (~95%) are caused by mutations in the CYP21A2 gene, which encodes steroid 21-hydroxylase. CAH patients manifest a wide phenotypic spectrum according to their degree of residual enzyme activity. CYP21A2 and its pseudogene (CYP21A1P) are located 30 kb apart in the 6q21.3 region and share approximately 98% of their sequences in the coding region. Both genes are aligned in tandem with the C4, SKT19, and TNX genes, forming 2 segments of the RCCX modules that are arranged as STK19-C4A-CYP21A1P-TNXA-STK19B-C4B-CYP21A2-TNXB. The high sequence homology between the active gene and pseudogene leads to frequent microconversions and large rearrangements through intergenic recombination. The TNXB gene encodes an extracellular matrix glycoprotein, tenascin-X (TNX), and defects in TNXB cause Ehlers-Danlos syndrome. Deletions affecting both CYP21A2 and TNXB result in a contiguous gene deletion syndrome known as CAH-X syndrome. Because of the high homology between CYP21A2 and CYP21A1P, genetic testing for CAH should include an evaluation of copy number variations, as well as Sanger sequencing. Although it poses challenges for genetic testing, a large number of mutations and their associated phenotypes have been identified, which has helped to establish genotype-phenotype correlations. The genotype is helpful for guiding early treatment, predicting the clinical phenotype and prognosis, and providing genetic counseling. In particular, it can help ensure proper management of the potential complications of CAH-X syndrome, such as musculoskeletal and cardiac defects. This review focuses on the molecular pathophysiology and genetic diagnosis of 21-hydroxylase deficiency and highlights genetic testing strategies for CAH-X syndrome.